Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Badan Kesatuan Bangsa Dan Politik Provinsi Lampung - Safitri, Nita Dwi; Selamat, Selamat (Utami Publisher, 2025)
The research investigates the less than optimal performance of employees of Badan Kesatuan Bangsa dan Politik Provinsi Lampung. It consists of three variables, namely, organizational culture, work discipline, and employee performance. The research aims to find about the levels of organizational culture, work discipline, and employee performance. In addition, it intends to find about the influence of organizational culture on employees performance, the influence of work discipline on employee performance, and the influence of organizational culture and work discipline on employee performance at the Badan Kesatuan Bangsa dan Politik Provinsi Lampung. The aim of this research is to determine the influence of organizational culture and work discipline on employee performance. The hypothesis in this research is that there is an influence of organizational culture and work discipline, both partially and simultaneously, on employee performance. The sample in this study consisted of 43 employees. Data collection techniques include observation, documentation and questionnaires. The data analysis method uses a quantitative approach with the help of SPSS version 21.0 statistical tools including calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and coefficient of determination tests. The results of hypothesis testing show that the organizational culture partially has a positive effect on employee performance. work discipline has a positive effect on performance. Simultaneous hypothesis testing shows that the organizational culture and work discipline together have a positive effect on performance with a contribution of 87,5%, while the remaining 12,5% is a variation of other variables outside this research.